Multimedia interactive application (MyInfaq) / Mohamad Hafiz Rashid - Rashid, Mohamad Hafiz (2022)
Infaq comes from a word that means producing something (wealth) for something, the amount of voluntary expenditure is not specified and time. According to Monzer Kahf, the Infaq Institution is one of the main pillars of the system Islamic economy and Islam as a reliqion / belief and way of life. Literally, Infaq is the Arabic word for expense.